On-line monitoring system in greenhouse area for chrysanthemum cultivation based on raspberry pi and iot. Issue 1 (March 2021) - Riskiawan, H Y; Anwar, S; Kautsar, S; Setyohadi, D P S; Arifin, S
Abstract: Chrysanthemum plants generally grow well when cultivated at an altitude of 650-1200 m above sea level. Chrysanthemum plants come from subtropical climates, with temperatures ranging from 17-30 C. whereas, in Indonesia, which is a tropical region, it is 20-26 C. The humidity needed by chrysanthemum plants at the time of planting is 90-95%, while at the time of enlargement and chrysanthemum flower growth of 70-80%. To get optimal results, chrysanthemum plants need to be cultivated in a greenhouse area. In a greenhouse, temperature and humidity can be controlled. In addition, chrysanthemum plants are also more protected from pests. In this paper, an on-line greenhouse monitoring system is developed. The system is equipped with sensors for temperature, humidity, soil humidity, light intensity, and an RGB camera. Sensor data is sent to the cloud database via raspberry pi. Data is displayed in graphical form every 1 hour. The sensor data can be accessed from anywhere via the internet network and can be used for the analysis of crop yields based on greenhouse conditions during cultivation.